FORMULASI GEL EKSTRAK PATIKAN KEBO (Euphorbia hirta L.) DAN UJI AKTIVITAS TERHADAP BAKTERI Staphylococcus epidermidis - Tri Novrianti Djanggola; Yusriadi Yusriadi; Muhamad Rinaldhi Tandah (Universitas Tadulako, 2016)
Patikan kebo (Euphorbia hirta L.) is a plant that have activity of inhibiting the Staphylococcus epidermidis bacteria, which was known as the cause of acnes. Flavonoids and tannin as antibacterial compounds which supposedly can act as an active antiacne. Purposes of this research is formulating extract gel of patikan kebo and antibacterial activity against Staphylococcus epidermidis by agar difussion method using paper disc and to know stability of the gel. The result was analyzed by One Way ANOVA with confidence level of 95%, followed by Duncan test. The result of this research showed test antibacterial activity that difference among the concentration extract has a noticeable difference zone of inhibition and extract gel of patikan kebo not have good physical quality during 28 days of storage. Keywords: Patikan kebo (Euphorbia hirta L.), gel, antibacterial, Staphylococcus epidermidis